Penerapan E-Government melalui Aplikasi Masagi Musrenbang di Desa Ciburial - Abubakar, Rodlial Ramdhan Tackbir; Prasetya, Dimas Dwi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2025)
The Ciburial Village Government has developed an innovation in order to make changes to the process of compiling a list of community proposals in the Village Development Planning Deliberation (Musrenbang Desa) process, namely through the Masagi Musrenbang application. The Masagi Musrenbang application is a website-based application used to input, store, and inform a list of community proposals through the RW head based on the results of deliberations at the RW level for the purposes of compiling village planning. This study aims to determine the utilization, obstacles and efforts that can be made in the utilization of the Masagi Musrenbang application in Ciburial Village in terms of the success factors of e-Government implementation. This study uses a descriptive qualitative approach. Data collection in this study was carried out through interviews, observations, and documentation studies. The results of this study indicate that the use of the Masagi Musrenbang application in Ciburial Village shows a positive step in the effort to digitize village development planning in a participatory manner. This application has supported the process of inputting community proposals through the RW Head, although it still faces a number of obstacles such as limited human resource capacity, internet infrastructure constraints, differences in user devices, and budget limitations. There are several efforts to support the utilization of the Masagi Musrenbang application produced in this study, including: The Ciburial Village Government needs to immediately strengthen the institution by establishing a clear division of tasks related to the management of the Masagi Musrenbang application and allocating a special budget in the Village Budget for the development and maintenance of the application.